Contribution of internal audit in procurement of goods and services at the President’s Office (PO), Constitution, legal affairs, public service and good governance-Zanzibar - Kheir, Abdalla (Mzumbe University, 2024)
A dissertation submitted to School of Business in the partial fulfillment of the requirement for award of the Degree of Master in Accounting and Finance of Mzumbe University